2014
DOI: 10.1093/ije/dyu191
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of telomere length assessment: an international collaborative study

Abstract: Background: Telomere length is a putative biomarker of ageing, morbidity and mortality. Its application is hampered by lack of widely applicable reference ranges and uncertainty regarding the present limits of measurement reproducibility within and between laboratories.Methods: We instigated an international collaborative study of telomere length assessment: 10 different laboratories, employing 3 different techniques [Southern blotting, single telomere length analysis (STELA) and real-time quantitative PCR (qP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 31 publications
6
130
0
Order By: Relevance
“…Finally, the direct correlation between qPCR T/S ratio and Southern telomere kbp length results were modest, and non significant in controls; the confirmatory qPCR was also performed later at a different laboratory. It is worth noting that prior studies have also found wide variability in absolute results across laboratories, though standardized values examined as ranks were highly correlated, significant variance across labs remained and was largely explained by differences in qPCR and gel based methods (Martin-Ruiz et al, 2014)…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the direct correlation between qPCR T/S ratio and Southern telomere kbp length results were modest, and non significant in controls; the confirmatory qPCR was also performed later at a different laboratory. It is worth noting that prior studies have also found wide variability in absolute results across laboratories, though standardized values examined as ranks were highly correlated, significant variance across labs remained and was largely explained by differences in qPCR and gel based methods (Martin-Ruiz et al, 2014)…”
Section: Discussionmentioning
confidence: 99%
“…Further, insufficient calibration of assay methods across labs and the lack of accepted “normal ranges” for LTL and PBMC basal TA make it premature for cell aging markers to enter clinical use at this time (Martin-Ruiz et al, In press). The relatively small effect sizes reported in reviewed positive studies, as well as the lack of diagnostic specificity of LTL and PBMC basal TA changes, also argue against the use of such markers as diagnostic tools, in isolation from other measures, at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Pooling data across studies and laboratories can be complex due to methodological differences in measuring telomere length. 37 In the current study, all samples were analysed together in the same laboratory using the same analytic protocol. Confounding by exposures such as smoking and obesity may affect associations.…”
Section: Discussionmentioning
confidence: 99%